Mongolia Agricultural Productivity and Marketing - Rasmussen, Debra; Annor-Frempong, Charles (World Bank, Washington, DC, 2015)
Mongolia’s ongoing economic transition generates levels of uncertainty that often inhibit investments in productivity and marketing improvements on the part of producers and processors. This study was undertaken to identify gaps in policies, laws, regulations, and practices from production to the consumer end point, and to stimulate discussions about how to leverage the agriculture sector’s potential contributions to national development objectives.